An APPLICATION OF SURFACE CONSISTENT AMPLITUDE CORRECTION (SCAC) IN THE "HRNR" FIELD - Yatini, Y; Nur Rohman, Hafid Rizki (Indonesian Applied Physics Letters, 2024)
This research aims to enhance the quality of 3D onshore seismic data and understand subsurface structures in a study area. We implemented the Surface Consistent Amplitude Correction (SCAC) method in seismic data processing. This study's results demonstrate that using SCAC significantly improves the quality of seismic data amplitudes, especially in eliminating previously disruptive noise in the analysis. Following the application of SCAC, seismic data amplitudes become clearer and stronger. The interpretation of the enhanced seismic data with SCAC revealed the presence of a significant geological structure, namely a reverse fault, which has significant implications for subsurface understanding. The location of this reverse fault was identified at inline 190 within the CMP range of 60 to 120, with time domain depths ranging from 150 ms to 1250 ms in the southwestern part of the cross-section. This research highlights that SCAC plays a key role in enhancing seismic data resolution and enables the identification of reverse faults that were previously challenging to discern. These findings make a crucial contribution to understanding subsurface geology in the study area and hold significant potential in the context of natural resource exploration. This study firmly establishes that SCAC is an effective tool in improving seismic data quality and revealing important geological structures, especially reverse faults, which can be a primary focus in subsurface geological studies in this research area.